Pengaruh Persepsi Kemudahan, Persepsi Kegunaan dan Persepsi risiko terhadap Minat Menggunakan Kartu Kredit (Studi pada pengguna kartu kredit di lingkungan PT Bank OCBC Nisp) - Dita Nur Ikhsana Hidayati (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of perceive ease to use, perceive usefulness and perceive risk on intention to use credit cards. The research was conducted quantitatively by survey method using questionnaire. The sample of research was credit card users who happened to be encountered in the environment of PT Bank OCBC Nisp counted 96 people. Sampling technique was accidental sampling technique. Data were analyzed by using multiple linear regression analysis. The results showed that the perceive ease to use, perceive usefulness and perceive risk had a significant influence on the intention to use credit cards. The perceive ease to use, perceive usefulness and perceive risk had contributed 71,2% in influencing intention to use credit card to customers and employees of PT Bank OCBC nisp. Keywords: perceive ease to use, perceive usefulness and perceive risk